Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.2903/j.efsa.2018.5484
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium citrate malate as a source of magnesium added for nutritional purposes to food supplements

Abstract: The present scientific opinion deals with the assessment of the bioavailability of magnesium, from the proposed nutrient source, magnesium citrate malate (MgCM), when added for nutritional purposes to food supplements. MgCM is a mixed salt consisting of magnesium cations and citrate and malate anions, and with a magnesium content of 12-15%. MgCM is proposed to be used in food supplements that are intended to provide up to 300-540 mg/day magnesium. The data provided demonstrate that the production process resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Supplements may contain mixed salt of magnesium citrate and malate, with a magnesium content of 12–15%, a mixed salt formulation suggested to be used in food supplements that are intended to provide up to 300–540 mg/day magnesium. The EFSA panel concluded that it is a source from which magnesium is bioavailable, but the extent of its bioavailability still remains unclear [ 212 ].…”
Section: Nutritional Strategies To Avoid Magnesium Deficienciesmentioning
confidence: 99%
“…Supplements may contain mixed salt of magnesium citrate and malate, with a magnesium content of 12–15%, a mixed salt formulation suggested to be used in food supplements that are intended to provide up to 300–540 mg/day magnesium. The EFSA panel concluded that it is a source from which magnesium is bioavailable, but the extent of its bioavailability still remains unclear [ 212 ].…”
Section: Nutritional Strategies To Avoid Magnesium Deficienciesmentioning
confidence: 99%
“…For the principle of electrode selection, the primary consideration is biocompatibility. The human body has upper daily intake limits for metal trace elements, such as Mg (300 mg day –1 ), Zn (15 mg day –1 ), Mn (5 mg day –1 ), Fe (12 mg day –1 ), Cu (2 mg day –1 ), and Mo (0.3 mg day –1 ) (Figure a). At the same time, all the above metal materials have a certain degradation rate, so that these metals and their oxides (MoO 3 and MnO 2 ) can be implanted as electrodes into the human body under the control of the total amount . In addition, some conductive carbon-based materials, such as polypyrrole (PPy), graphene, etc., have excellent biocompatibility and can be used as electrodes for degradable batteries.…”
Section: Aqueous Battery For Implantable Electronic Devicesmentioning
confidence: 99%
“…The low Mg level in the body is due mainly to a decreased intake, being correlated with a diet consisting of high quantities of processed foods, as well as vegetables or fruits, which have been grown using various substances that decrease mineral concentrations [30]. Other risk factors include smoking, alcohol consumption, stress, chronic fatigue and various renal and gastrointestinal disorders that negatively influence Mg reabsorption [14,19,44]. In order to combat Mg deficiency, it is recommended to use food supplements containing in various Mg compounds (i.e., orotate, carbonate, oxide, lactate, citrate, hydroxide) in different concentrations.…”
Section: Introductionmentioning
confidence: 99%